Enhancing Sustainability With Triple-Layered Business Model Canvas in Gastronomy Agro-Tourism Sukajadi Village Bogor - Hastjarjo Hastjarjo (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Developing more sustainable business models (BM) has become increasingly crucial for sustaining the agro-tourism industry as environmental and social pressures increase. However, sustainable business modeling is still underused in the development of agro-tourism.Purpose: This research aims to explore a new approach for transitioning towards a more sustainable BM in agro-tourism, with a case study in Sukajadi Tourism Village, Bogor.Design/methodology/approach: The method used in this research is action research with the 3E process (explore, exploit, enhance). The hypothetical business model canvas is explored as an initial step, then the SWOT sustainability framework is used in the exploration stage, and finally, the Triple Layered Business Model Canvas (TLBMC) framework is used to synthesize the previous two steps in the improvement stage.Findings/Result: The results of the study show that, overall, the TLBMC framework enables creative process guidance in communicating and implementing business improvement models (BM), from conventional gastronomic agro-tourism to gastronomic permaculture. The new SBMC resulted from the expansion of the domain to increase the agro-tourism value proposition in terms of sustainability targets and is expected to be in accordance with the environmental potential and wishes of the Sukajadi Village Community, Bogor.Conclusion: TLBMC can be implemented to increase sustainability in the Sukajadi Tourism Village. The results of the analysis recommend the development of permaculture-based gastronomic agro tourism.Originality/value (State of the art): This research contributes to the TLBMC theory in the development of agro-tourism villages.